FITNESS WEAR: THE CONSTRUCTION OF THE FEMALE BODY (Fiep Bulletin - online, 2013)
This study analyzed the effect of mass media, particularly health and beauty magazines, on the construction and maintenance of current female aesthetic standards. The body is covered with meaningful elements in current society, and is read as a discourse full of intensions that reflect current social characteristic, social ideals, culture and values. Fitness wear, the object of analysis of this study, is one of the tools used by ads in the construction of such body.
Keywords: Mass media; female body; aesthetic standards